PENGARUH KEBIJAKAN HUTANG, KEPUTUSAN INVESTASI, DAN TOTAL ARUS KAS TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2011-2014) - Devy Sari Apriyani, 10.05.52.0196; Himawan, Arief (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to examine and analyze the effect of the debt policy, investment decision, and the total cash flow to the firm value . Every company has a goal to maximize the welfare of the owners by raising the value of the company. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange period 2011-2014. The sampel was conducted using purpose sampling. The samples used were 101 manufacturing companies. The data used is secondary data abtained from the Financial Statements and the Indonesia Capital Market Directory (ICMD). The analysis technique used is multiple linear regression analysis. The results of this study indicate that the debt policy, investment decisions, and total cash flow significant negative effect on the value of the company. Keywords: Debt Policy, Investment Decision, Total Cash Flow, Enterprise Value